Assessment of epidemiological and epizootiological situation on tularemia in the Republic of tatarstan - T. A. Savitskaya; V. P. Popov; V. A. Trifonov; I. V. Milova; G. Sh. Isaeva; I. D. Reshetnikova (Проблемы особо опасных инфекций, 2018)
Objective of the study was to assess epidemiological and epizootiological activity of natural tularemia foci in the Republic of Tatarstan for further forecasting of the developments and working out the tactics for implementation of preventive and anti-epidemic measures. Materials and methods. We utilized statistical data, reports of the Center of Hygiene and Epidemiology in the Republic of Tatarstan, and literature sources for the analysis. Results and conclusions. Since 1995, the incidence among the population in Tatarstan has not been registered. Natural tularemia foci are situated in 19 enzootic as regards the infection administrative districts in the territory of the Republic. Epizootiological monitoring of the natural foci suggests that over the last four years their activation occurred. In this contest realization of complex anti-epidemic  measures,  regulated  by  the  current  normative-methodological  documents  remains  relevant,  as  well  as timely and effective diagnostics, including among the patients with a similar to tularemia symptoms.